Flat sheet membrane elaboration by TIPS method using palm oil as solvent and its application in membrane distillation (2017)
(Eng) Palm oil (PO) was used as new solvent for the elaboration of low density polyethylene (LDPE) flat sheet membranes via TIPS method. Phase diagram LDPE/PO was determined, and the effect of parameters such as polymer content (20, 30% w/w), temperature of coagulation bath (0, 25°C) and polymer size (#12, #6 mesh) on thickness, pore size, water vapor permeability and water intrusion pressure of the LDPE membranes was studied. The only parameter that significantly affects the membrane characteristics was polymer content (exempting thickness membrane). By an increase of polymer content, pore size and water vapor permeability decrease (2.7 and 1.2 times, respectively), while water intrusion pressure increases (>1.2 times). Membranes with a thickness of less than 400 µm and pore sizes between 2.3 and 0.8 µm were obtained. Membranes with 0.8 µm pore size were selected to concentrate ethanol-water and glucose solutions by vacuum membrane distillation. Membranes permeated 0.0667 and 0.0508 mol.m-2.s-1, respectively in 2 h of experimentation. Moreover, a 2.1 concentration factor was found using ethanol-water solutions.